Modulation of UVB-induced inflammation and oxidative stress by unfermented rooibos and honeybush aqueous extracts: A comparative study - Keet, Lana (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.